ANALISIS PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN INTERNAL AUDIT TERHADAP FEE AUDIT EKSTERNAL (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Muh Naharul Karim, 12.05.52.0250; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This study aimed to analyze the influence of corporate governance structure and internal audit of the audit fee on companies listed in Indonesia Stock Exchange period 20122014. In this study, researchers used a data sample of financial companies listed on the Stock Exchange during the years 2012-2014 as many as 58 companies. The sampling method used is purposive sampling method. The analysis tool in this study using multiple linear regression. The result of this research is the independence of the board of directors, audit committee independence, the number of audit committee, audit committee meetings and the intensity of the internal audit does not affect the audit fee. While the number of commissioners positive effect on audit fee which means the higher the number of commissioners, the audit fee will increase.  Keywords: The Independence of The Board of Directors, The Number of Commissioners, The Independence of The Audit Committee, The Number of Audit Committee, The Intensity of The Audit Committee Meetings, Internal Audit, The Audit Fee